The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1477-9552.12217
|View full text |Cite
|
Sign up to set email alerts
|

EU‐wide Economic and Environmental Impacts of CAP Greening with High Spatial and Farm‐type Detail

Abstract: In this paper we analyse the economic and environmental impacts of CAP greening introduced by the 2013 CAP reform using the CAPRI model. CAPRI captures the farm heterogeneity across the EU and it allows to depict the implementation of the greening measures in high detail while integrating the environmental effects and the market feedback of the simulated policy changes. The simulated results reveal that the economic impacts (land use, production, price and income) of CAP greening are rather small, although som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 24 publications
3
70
1
2
Order By: Relevance
“…Consistency between the document-based evaluation and the group evaluation confi rm the importance of formal intervention logic for actual quality of intervention. Ex ante studies of the CAP 2014-2020 argued that the reform would not bring any major changes (Gocht et al, 2016), and even indicated that intervention logic was reversed, i.e. that objectives were set to legitimise an existing intervention based on distribution logic (Erjavec et al, 2015), whereas ex post impact assessments of CAP 2014-2020 confi rm the main arguments of this research, including the positive but costly 'secondary' effects, e.g.…”
Section: Conclusion: Decentralising Responsibilitymentioning
confidence: 63%
See 1 more Smart Citation
“…Consistency between the document-based evaluation and the group evaluation confi rm the importance of formal intervention logic for actual quality of intervention. Ex ante studies of the CAP 2014-2020 argued that the reform would not bring any major changes (Gocht et al, 2016), and even indicated that intervention logic was reversed, i.e. that objectives were set to legitimise an existing intervention based on distribution logic (Erjavec et al, 2015), whereas ex post impact assessments of CAP 2014-2020 confi rm the main arguments of this research, including the positive but costly 'secondary' effects, e.g.…”
Section: Conclusion: Decentralising Responsibilitymentioning
confidence: 63%
“…Member states have little experience with the programming of Pillar I. The 'greening' of the direct payment system, introduced in 2014-2020, which involved certain fl exibility and required some planning at the national level, was deemed too complicated by some member states and later largely failed in terms of the environmental objectives it aimed to pursue (Gocht et al, 2016). Eco-schemes, which will upgrade the 'greening' component in Pillar I, are more fl exible but, potentially, also more complex.…”
Section: Administrative Capacitymentioning
confidence: 99%
“…At UE-level, Gocht et al (2017) analysed the economic and environmental impacts of CAP greening introduced by the 2013 CAP reform using the CAPRI model. Their results show that the environmental impacts of greening are small, although greater effects can be pointed out in the regions with a larger percentage of intensive farms [17].…”
Section: Literature Review On Greeningmentioning
confidence: 99%
“…At UE-level, Gocht et al (2017) analysed the economic and environmental impacts of CAP greening introduced by the 2013 CAP reform using the CAPRI model. Their results show that the environmental impacts of greening are small, although greater effects can be pointed out in the regions with a larger percentage of intensive farms [17]. Louhichi et al (2017), using an EU-wide individual farm level model, show that the effects of the crop diversification practice on the EU farming sector are rather small.…”
Section: Literature Review On Greeningmentioning
confidence: 99%
“…EU funding sources (and in particular the Common Agricultural Policy) are important for the management of agricultural habitats in Natura 2000 sites. Funding for agriculture already has declined for several years, whilst attempts to increase funding for environmentally-friendly agricultural management have met limited success (Gocht et al, 2017;Pe'er et al, 2017). The foreseen reallocation of budgets will further decrease the funding for agriculture (European Commission, 2018).…”
Section: Synthesismentioning
confidence: 99%